1993
DOI: 10.1007/bf00308614
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in experimental spinal cord injury: time-level relationship

Abstract: Damage which occurs following spinal traumas is often irreversible. During recent years free oxygen radicals formed due to the pathological changes following neural tissue ischemia have been identified as being responsible for the ethio-pathogenesis of such damage. In our experimental study, model lesions are formed in spinal cords of rats by standard trauma. Malondialdehyde (MDA), a lipid peroxidation product, was measured in the spinal tissues distal to the trauma in order to examine indirectly the time-quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 46 publications
0
42
0
4
Order By: Relevance
“…4,5 The extent of lipid peroxidation is a useful parameter for evaluating cellular disturbances caused by spinal cord trauma under experimental conditions. [32][33][34] The literature mentioned above outlines the biochemical basis and evidence for the occurrence of oxygen radical generation and lipid peroxidation during the acute phase of central nervous system (CNS) trauma or stroke (ischemic and hemorrhagic).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The extent of lipid peroxidation is a useful parameter for evaluating cellular disturbances caused by spinal cord trauma under experimental conditions. [32][33][34] The literature mentioned above outlines the biochemical basis and evidence for the occurrence of oxygen radical generation and lipid peroxidation during the acute phase of central nervous system (CNS) trauma or stroke (ischemic and hemorrhagic).…”
Section: Discussionmentioning
confidence: 99%
“…36,39 ± 42 It was shown that lipid peroxidation levels reached its maximum at 1 h after experimental spinal cord injury. 39 Therefore, we have started the cooling procedure 30 min after the injury and continued for 30 min. Perfusion of the injured or ischemic spinal cord with a cool, isotonic solution has been used in animal models 1,3,6 and humans and has shown some promise.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of MDA were also seen in the contused rat spinal cord as early as 30 minutes post-SCI, which peaked at 3 h and returned to baseline by 12 h [26]. In a compression SCI model, MDA was significantly increased by 15 minutes, peaked at 1 h and then fell thereafter [122], suggesting that there is not much difference between the cat contusion and rat compression models at least as far as the onset of post-SCI LP. However, two unfortunate limitations of these studies were the choice of MDA, which is a biomarker of enzymatic LP during the arachidonic acid cascade, as well as free radical-induced LP, and the fact that postinjury times longer than 12 h were not included.…”
Section: Onset and Duration Of Oxidative Damage In The Injured Spinalmentioning
confidence: 99%